Dissection of genetic variation and evidence for pleiotropy in male pattern baldness. Issue 1 (December 2018) - Yap, Chloe; Sidorenko, Julia; Wu, Yang; Kemper, Kathryn; Yang, Jian; Wray, Naomi; Robinson, Matthew; Visscher, Peter
Abstract Male pattern baldness (MPB) is a sex-limited, age-related, complex trait. We study MPB genetics in 205, 327 European males from the UK Biobank. Here we show that MPB is strongly heritable and polygenic, with pedigree-heritability of 0.62 (SE = 0.03) estimated from close relatives, and SNP-heritability of 0.39 (SE = 0.01) from conventionally-unrelated males. We detect 624 near-independent genome-wide loci, contributing SNP-heritability of 0.25 (SE = 0.01), of which 26 X-chromosome loci explain 11.6%. Autosomal genetic variance is enriched for common variants and regions of lower linkage disequilibrium. We identify plausible genetic correlations between MPB and multiple sex-limited markers of earlier puberty, increased bone mineral density (r g = 0.15) and pancreatic β-cell function (r g = 0.12). Correlations with reproductive traits imply an effect on fitness, consistent with an estimated linear selection gradient of -0.018 per MPB standard deviation. Overall, we provide genetic insights into MPB: a phenotype of interest in its own right, with value as a model sex-limited, complex trait. Male pattern baldness (MPB) is a polygenic trait that affects the majority of European men. Here, Yap et al. estimate heritability, partitioned by autosomes and the X-chromosome, of MPB in the UK Biobank cohort, perform GWAS for MPB and find genetic correlation with other sex-specific traits.